(untitled) (Journal of the College of Basic Education, 2022)
The cognitive transformation and technological development is a source of charging the artist with a new vision that motivates him to select new ideas that are consistent in terms of their meaning, concept, and modern visual orientation. General and plastic work in particular, and witnessed transformations in the concept of fine arts to keep pace with intellectual and technological development.